ANÁLISE DA EFICIÊNCIA DE REMOÇÃO DE FERRO E MANGANÊS DE ÁGUAS DE ABASTECIMENTO POR FILTRAÇÃO ADSORTIVA - PAZ, ELAINE CARVALHO DA (2016)
The present study evaluates the iron removal efficiency (Fe), manganese (Mn), apparent color and turbidity, using adsorptive filtration compared with conventional filtration, using a natural Zeolite as layer second material in a pilot unit with constructive and operational typology similar to the rapid downward filter, gravity and double layer. As adsorbent material was selected Zeolite WATERCELL-ZF-0410®, commercially available Clinoptilotite from Cuba, for having physical characteristics similar to the anthracite coal. Morphological characterization assays were performed (FEG-SEM) and elemental (EDS), physical characteristics (particle size, density, effective size and uniformity coefficient), lixiviation and filtration on a pilot scale. Morphological characterization analysis, it was found that the zeolite under consideration has a high adsorption capacity, prone to adsorption iron, manganese and sulfur in the upper range anthracite coal. The physical characterization analysis, it was verified that this Zeolite is a uniform material and graduated, has physical similarity to the coal and anthracite can be used as filtering material of the layer second. Leaching analysis showed that, possibly, there will be no release above the maximum value allowed in CONAMA Resolution n. ° 357/2005, metals detected in the leached extract for a backwashing of filter using this material as media filter, as well as probably not occur detachment of these metals in the final disposal of this waste system. The filtration analysis on a pilot scale concluded that designing a filter with downward filtration, with depth action and double layer using the Zeolite WATERCEL-ZF-0410 on the layer second, is viable. The conception of treatment proposed, in the conditions, parameters and settings studied, has average efficiency: 100.00% for the removal of manganese; 96.17% for the removal of iron; 99.90% for the removal of apparent color; and 98.96% for the removal of turbidity.